2018
DOI: 10.1111/jcpe.12930
|View full text |Cite
|
Sign up to set email alerts
|

Salivary exRNA biomarkers to detect gingivitis and monitor disease regression

Abstract: The clinical values of the developed salivary exRNA biomarkers are associated with gingivitis regression. They offer strong potential to be advanced for definitive validation and clinical laboratory development test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…Thus, there is now compelling evidence that miRNAs are associated with physiological and pathological process that contribute to the development and progression of systemic diseases, such as cancers [33] and vascular disease [34], as well as periodontal disease [22,35]. Several studies described the potential of miRNAs as putative diagnostic biomarkers for periodontal disease, including hsa-miR-15a-5p, hsa-miR-29b-3p, hsa-miR-124-3p, hsa-miR-140-5p, hsa-miR-146a-5p, hsa-miR-148a-3p, hsa-miR-155-5p, hsa-miR-223-3p, hsa-miR-301b, hsa-miR-628-5p [21][22][23][24][25][26]. It has been reported that hsa-miR-140-5p and hsa-miR-628-5p in gingival crevicular fluid are potential diagnostic biomarkers for periodontitis [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is now compelling evidence that miRNAs are associated with physiological and pathological process that contribute to the development and progression of systemic diseases, such as cancers [33] and vascular disease [34], as well as periodontal disease [22,35]. Several studies described the potential of miRNAs as putative diagnostic biomarkers for periodontal disease, including hsa-miR-15a-5p, hsa-miR-29b-3p, hsa-miR-124-3p, hsa-miR-140-5p, hsa-miR-146a-5p, hsa-miR-148a-3p, hsa-miR-155-5p, hsa-miR-223-3p, hsa-miR-301b, hsa-miR-628-5p [21][22][23][24][25][26]. It has been reported that hsa-miR-140-5p and hsa-miR-628-5p in gingival crevicular fluid are potential diagnostic biomarkers for periodontitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the potential of miRNAs as putative diagnostic biomarkers for periodontal disease, including hsa-miR-15a-5p, hsa-miR-29b-3p, hsa-miR-124-3p, hsa-miR-140-5p, hsa-miR-146a-5p, hsa-miR-148a-3p, hsa-miR-155-5p, hsa-miR-223-3p, hsa-miR-301b, hsa-miR-628-5p [21][22][23][24][25][26]. It has been reported that hsa-miR-140-5p and hsa-miR-628-5p in gingival crevicular fluid are potential diagnostic biomarkers for periodontitis [25]. Evidence demonstrated hsa-miR-146a-5p might serve as an indicator for periodontal disease severity in both gingival tissues [36] and saliva [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] Many of the diagnostics surveyed fell into this category. PM/PD diagnostics play a signiicant predictive role especially with those measuring predictive biomarkers, which consider speciic risk factors, genetic phenotype, pharmacokinetic characteristics, and other features unique to each patient.…”
Section: Use Of Pm/pd Diagnostics In Clinicsmentioning
confidence: 99%
“…The 2017 survey extended the 2014 survey by investigating the use in DDS/DMD and postgraduate/resident program clinics of seven genetics-based and eight non-genetics-based PM/PD diagnostics kinetic characteristics, and other features unique to each patient. [14][15][16][17][18] Many of the diagnostics surveyed fell into this category. The survey found that Oral DNA Genetics Labs and Periopredict were the two most popular genetics-based PM/PD clinical diagnostic used in these schools, with 5% of participating DDS/DMD programs and 14% of participating postgraduate/ resident programs using OralDNA Labs and 14% of participating postgraduate/resident programs using Periopredict (Figure 2, panel A).…”
Section: Use Of Pm/pd Diagnostics In Clinicsmentioning
confidence: 99%